Revisita ao exercício de projecto. Experiência entre escolas de arquitectura - Raquel Hespanhol Peixoto de Babo (2019)
"Revisit to the project exercise. Experience between schools of architecture" marks a point of transition of a process, long and still initial, in the learning of the architecture. In this phase of change we propose a reflection, a revisit, to this journey and to the experiences that shape it, with the aim of trying to understand some of our choices. This journey is shaped by the constant practice and study of the project, as a common point and meeting between the two schools that characterize the synthesis of our learning - the Faculty of Architecture of the University of Porto and the Accademia di Architettura de Mendrisio. The experience in the Accademia de Mendrisio motivates this revisit by the confrontation with another practice, and teaching, that awoke a constant questioning to the project, associated to a feeling of anguish, inherent of the creation process. It is proposed, therefore, the reunion with the exercise developed in another school, the return to the same problem, now in a selfcritical position, with a distance. It is our goal to resume that journey, allowing us, for the first time, a critical reflection and awareness of the actions and decisions of the project. We will try to find justifications for that feeling of nonconformity and try to understand to what extent the course of learning in a school influenced that new experience. This revisit implies, however, some preparation: study the place of departure to better understand the places we passed during the journey and finally return. This is the course that we decided to do, although we know that we are always talking about the same place. We are placed between our schools and choices, Porto School (FAUP) and Mendrisio School (AAM), two institutions dedicated to teach the study and practice of an idea of architecture, whose synthesis will certainly reveal our Place, today.